The True Jesus : uncovering the divinity of Christ in the gospels - Limbaugh, David (Washington, D.C : Renery Publishing, 2017)
"Who do you say that I am?" Uttered by Jesus Christ, this profound question has presented an age old challenge to believers, skeptics, scholars, and rulers. In attempting to answer this question, The True Jesusgoes straight to the unimpeachable source: the books of Matthew, Mark, Luke, and John. Only in the Gospels, says author David Limbaugh, do we com face to face with the Son of God, Whose sublime teachings, miraculous actions, and divine essence leap off every page and into our hearts. In this book, Limbaugh combines the four Gospel stories into a unified account (though not, he humbly admits, a perfect harmony) and guides readers on a faith journey through the Four Evangelists' testimonies of the life of JesusChrist. Along the way, Limbaugh shares his insights on Jesus' words and deeds as well as His unique nature as fully human and fully divine. In The True Jesus, you will learn: Why even the apostles failed to completely understand Jesus' true identity and mission until after his crucifixion. Why Jesus selectively revealed His divinity instead of consistently proclaiming it. The real basis for the rejection of Jesus' message by skeptics in His hometown and elsewhere. The historic events preceding Jesus' birth that providentially paved the way for Christianity. How Jesus' message utterly contradicted modern attempts to portray him as being non-judgmental. Limbaugh's passion for the Gospels infuses the pages of The True Jesus, which is both a primer for new Bible readers and an outstanding guide to the Gospels for long-time believers. Who really is the trueJesus? Open this book and begin your odyssey toward the answer.
From Jesus' birth to His initial teachings-- From "Catching men" to the Golden rule-- From healing a Centurion's Servant to confrontations with Pharisees-- From the transfiguration to an argument over Abraham-- From healing a blind man to Mary's ointment-- From the plot to kill Lazarus to Peter's Ill-fated Vow-- From Jesus reassurance to Pilate's judgment-- From the flogging to Jesus to His Ascension
Keywords: Jesus Christ -- Biography -- History and Criticism; Jesus Christ -- Historicity; Bible. Gospels -- Criticism, interpretation, etc; Christianity